Clinical phase I/II trial of SVF therapy for cartilage regeneration: A cellular therapy with novel 3D MRI imaging for evaluating chondral defect of knee osteoarthritis - Ren, Bin; Chang, Yiqiang; Liu, Ruolan; Xiao, Feng; Xu, Jun; Li, Lingsong; Li, Tao; Ruan, Zhao; Bao, Yigui; Lin, Junbing; Zhou, Junying; Liao, Weijing; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: The clinical applications of stromal vascular fraction (SVF) therapy for osteoarthritis (OA) have attracted academic and clinical attention. However, data of the effects of SVF therapy on regeneration of degenerated cartilage are limited in the literature. Meanwhile, there is a great need for a simple and non-invasive evaluation method to analyze the changes of joint cartilage qualitatively and quantitatively in clinical trials. This study entitled “SVF Therapy for Human Knee Osteoarthritis” was registered in ClinicalTrial.gov # NCT05019378. Materials and Methods: We designed and conducted a single center, open labeled clinical phase I/II study, and 6 OA patients with both knee cartilage defect I-II were enrolled in this study. The two knees of each patient were randomly assigned to autologous SVF treatment group or non-treatment control group to evaluate the safety and therapeutic effect of SVF therapy for human knee OA. We have also established a novel protocol to provide 3D MRI imaging for human knee cartilage enabling us to qualitatively and quantitatively evaluate cartilage degeneration and regeneration in this study. Results: The qualitative and quantitative evaluation of 3D MRI imaging of knee cartilage demonstrated that the SVF therapy reduced the cartilage defects; and significant increase of cartilage value both in defect cartilage area and whole cartilage area of treated group and significant increase of thickness and area of both femoral and tibia cartilage in vertical sections of the SVF treated Group at 12W and 24W post treatment in cartilage defect I-II OA patients. Conclusion: This clinical phase I/II study indicated that SVF therapy is a safe clinical procedure and provided evidence that the SVF therapy significantly facilitated cartilage regeneration, opening the opportinity to a phase III trial investigating authentic efficacy of the procedure. This study is the first qualitative and quantitative evaluation of the efficacy of autologous SVF cellular therapy on cartilage regeneration. Through early and definite diagnosis of knee osteoarthritis patients, and providing safe and efficient therapy to facilitate cartilage regeneration, we will be able to control or reverse cartilage degeneration and completely change the epidemiology of OA worldwide.